Experimental investigation of maximum stress concentrations in a femur bone by photoelastic approach - Bruce Ralphin Rose J (Kuwait Journal of Science)
Progress in experimental stress analysis methods helps to understand the stress distribution in the bone structures that is essential to perform successful implants. Biomechanics requires professional methodologies to solve complex problems where the measurement of physical reactions caused by the loads is impractical in nature.  In the present work, the maximum stress distribution behavior of human Femur bone under the action of startling loads that are caused by accidents/sporting activities is investigated through photoelastic method. The experiments are done using a circular Polariscope at different input loads and boundary conditions. The stress concentration factor is computed through the fringe orders that are related to the stresses obtained from the model. A 2D scaled model of Femur bone is prepared using acrylic material to capture the stress field by optical illumination method. Photoelastic stress analysis reveals the maximum shear stress in the plane of the model and the principal stress difference with high reliability. The nominal stress magnitudes are computed from the fringe order by supplementary data and numerical analysis. State of stress in the Femur at different instances is captured through multiple oblique views of the isochromatic fringes. The novel fringe interpretation method facilitates to identify the suitable material for implants with high factor of safety at actual loading conditions.